Determination of minimal sequence for zearalenone aptamer by computational docking and application on an indirect competitive electrochemical aptasensor - Azri, Farah Asilah; Selamat, Jinap; Sukor, Rashidah; Yusof, Nor Azah; Ahmad Raston, Nurul Hanun; Eissa, Shimaa; Zourob, Mohammed; Chinnappan, Raja (Springer, 2021)
Aptamers are short single-stranded oligonucleotides (either DNA or RNA) that can fold into well-defined three-dimensional (3D) spatial structures which enable them to capture their specific target by complementary shape interactions. Aptamers are selected from large random libraries through the SELEX process and only a small fraction of the sequence is involved in direct docking with the target. In this paper, we describe the possible truncation variants of zearalenone (ZEA) aptamer which might be an effective binding region for the target. The originally selected zearalenone (ZEA) aptamer was 80-mer in length and shown to bind the target with a high affinity (Kd = 41 ± 5 nM). Herein, computational docking simulation was performed with 15 truncated variants to determine the predicted binding energy and responsible binding site of the aptamer-analyte complex. The results revealed that 5 truncated variants had binding energy lower than - 7.0 kcal/mol. Circular dichroism analysis was performed on the shortlisted aptamer and the conformational change of aptamers was observed with the presence of an analyte. Aptamer Z3IN (29-mer) was chosen as the most enhanced affinity for its target with a dissociation constant of 11.77 ± 1.44 nM. The aptamer was further applied in the electrochemical aptasensor of ZEA based on an indirect competitive format. The results demonstrated that the truncated aptamer leads to an enhancement of the sensitivity of the biosensor.